Radioiodine Therapy of Graves' Disease and the Uptake Paradox - Malapure, Sumeet Suresh (Indian J Nucl Med, 2020)
PURPOSE OF THE STUDY: Radioiodine ((131)I) therapy is approved and well-accepted modality for the treatment of hyperthyroidism. The dosage of (131)I for successful treatment is based on many factors; however, an objective tool to determine the dose was missing. In a retrospective study, we found that high (131)I uptake values required more dose to achieve desirable results contrary to the belief. MATERIALS AND METHODS: Clinically and scintigraphically proven Graves' disease patients with high (131)I uptake (>50%) were accrued for this study and block randomized into low-dose (Group I) and high-dose (Group II) groups. Low activity (5 mCi) was administered in Group I and higher activity (10 mCi) in Group II. The patients were followed up after 3 months with thyroid function tests to determine the outcome. RESULTS: A total of 344 patients were analyzed at the end of 3 months, with 174 in low-dose group and 170 in high-dose group. Euthyroidism/hypothyroidism was achieved in significantly higher number of patients as compared to the low-dose group. CONCLUSION: The higher dose of (131)I is required to achieve euthyroidism/hypothyroidism in patients with high (131)I uptake.